Gruesome spectacles: botched executions and America's death penalty - Sarat, Austin (Stanford Law Books, An Imprint of Stanford University Press, 2014)
"Gruesome Spectacles is a history of botched, mismanaged, and painful executions in the U.S. from 1890 to 2010. Using new research, Sarat traces the evolution of methods of execution that were employed during this time, and were meant to improve on the methods that went before, from hanging or firing squad to electrocution to gas and lethal injection. Even though each of these technologies was developed to 'perfect' state killing by decreasing the chance of a cruel death, an estimated three percent of all American executions went awry in one way or another. Sarat recounts the gripping and truly gruesome stories of some of these deaths - stories obscured by history and to some extent, the popular press"--Provided by publisher